Semiconductive-like behaviour and negative differential effect observed in self-assembled riboflavin layer on gold electrodes - Akmal Fathurrahman Zullkifli; Mohammad Nofil; Chethan C. Thimmarayappa; Prince Nishchal Narayanaswamy Elumalai; Sara Talebi; Mitsumasa Iwamoto; Vengadesh Periasamy (Heliyon)
Riboflavin or vitamin B2 plays significant roles in metabolic reactions and energy production, establishing it as an important research subject in biology and medicine. While there are numerous riboflavin-related publications in these fields, interrogation of its electronic properties in relation to the physiological function at the cellular level remains obscure due to technological challenges. However, progress in molecular electronics and the discovery of the semiconductor-like behaviour of biomolecules in recent times have initiated growing interest in exploring the electronic properties of these materials for potential bioelectronic device applications. In this work, we demonstrate novel semiconductor-like behaviour in riboflavin within a gold/Riboflavin/gold Schottky junction. We observed the occurrence of two negative differential resistance peaks at low voltages of 1.5 and 2.0 V, probably the first-ever report of this effect in a biomolecule. Interestingly, the proposed mechanism simulates a single Schottky junction behaviour despite the physical existence of two junctions. Solid-state parameters such as turn-on voltage, shunt resistance, and ideality factor were also calculated using Conventional and Cheung and Cheung’s methods. The results were highly characteristic to the riboflavin studied when compared to previous works on biomolecules. This opens up the possibility of developing solid-state sensors for electronically characterising biomolecules like vitamins to help advance our understanding of the electronic properties of these essential nutrients.